Régimen de control de la actividad turística sobre la base de lo establecido en el art. 52 de la ley de turismo del Ecuador - Pantoja Torres, Johanna Catalina (2015)
Article 1 of the Constitution of the Republic of Ecuador tells to Ecuador as a constitutional State of rights and justice and Article 3 tells the paramount duty of the state to ensure that all citizens enjoy the rights enshrined in the Constitution and the international instruments. Article 11 determines that the servants and public, administrative or judicial, servers are required to apply standard and the most favorable interpretation of their effective force. Similarly, Article 76 of the Constitution guarantees Ecuadorian citizens in processes which rights and obligations of any kind are determined, the law will ensure due process, therefore no citizen may be tried or punished for an act or omission that when you commit that referred in law and concluded that the law will establish due proportionality between offenses and criminal, administrative or other sanctions. The Constitution in Article 82 is clearly establishes the right to legal certainty which is founded on respect for the Constitution and the requirement that there are legal rules set, clear, public and applied by the competent authorities, in their Article 132 is determined as competence of the National Assembly to pass laws and general rules of common interest and specifies that will require legislation to criminalize violations and establish appropriate sanctions. The validity of the constitutional provisions cited above, the Tourism Law Article 52 states the general instruments for effective control of tourist activity, including written warnings, fines, closure of the establishment by the commission of minor offenses, serious and repeated without determining the type of offense and the penalty for the commission of the same. The current standard for the tourism sector does not specify the applicable sanction when a commercially through its representative either natural or legal persons who commit minor, proven, serious and repeated failures, and the application of sanctions, so to justify this and raise a legal proposal in this respect, this work has a broad theoretical basis, with results of field research, confirming the existence of the problem and confirm the appropriateness of making a proactive approach to reform the Act runs above tourism